A Validity and Reliability Study of the Engineering and Engineering Education Attitude Scale (EEAS) - Korkmaz, Ã–zgen; KösterelioÄŸlu, Meltem; Kara, Mehmet (International Journal of Engineering Pedagogy (iJEP), 2018)
In literature it was not possible to find a proven valid and reliable scale to measure students’ attitudes towards engineering profession and engineering education. The objective of present research is to provide a valid and reliable scale for measuring students’ attitudes towards engineering profession and engineering education. The sample group is composed of 650 students for the first application and 113 students for the second. In order to detect the validity of the scale, exploratory and confirmatory factor analyses, item factor total correlations, corrected correlations and item discriminations were conducted. In order to assess the reliability of the scale, the level of internal consistency and the stability levels were calculated. EEAS a five-point Likert-type scale and includes 17 items with two factors. The analyses provided evidence that EEAS is a valid and reliable scale that can be assuredly used to identify students’ attitudes towards engineering profession and education they receive.